The milk yield of Ukrainian Holstein is related to the immunobiological parameters of blood of calves - Mylostyvyi, Roman; Milostiviy, Roman; Milostivyiy, Roman; Mylostyvyi, R. V.; Милостивий, Роман Васильович; Antonenko, Petro; Antonenko, P. P.; Antonenko, P.; Антоненко, Петро Павлович; Kostyuk, Volodymyr; Костюк, Володимир Кіндратович; Vasylenko, Tetiana; et al. (Zachodniopomorski Uniwersytet Technologiczny w Szczecinie, 2018)
Reduction of productive longevity of dairy cows in conditions of industrial dairy complexes causes another problem, which is connected with the timely replenishment of the herd with calves for replacement. Therefore, the cultivation of repair heifers very great importance. Much attention is focused on early forecasting of the future productivity of calves for obtaining highly productive cows. At the same time, the rates of growth and development in ontogenesis are very often studied, and blood indicators are rarely evaluated. In the literature available to us, there is little information about the relationship between the indices of humoral and cellular immunity of calves with the future productivity of the cow. These indicators are traditionally used to characterize the immunobiological reactivity of an organism and the health of calves, and there is practically no information on their relationship to the productive longevity of a dairy cow. This is partly due to the difficulties associated with the duration of the research, since the cow must complete its productive life. A positive and reliable relationship is established between the immunobiological characteristics of calves' blood and their lifelong milk yield when they become a cow. The greatest correlation was noted between the indicators of milk productivity and bactericidal activity of blood serum (r = 0.63-0.69, P<0.05). The relationship between cellular factors of body defense (phagocytic activity of neutrophils) and the content of immunoglobulins of classes G and M with signs of milk productivity was less dense. It was, respectively, r = 0.31-0.41 and r = 0.58-0.63 (P<0.05). This makes it possible to conclude that the studies conducted in this direction are promising, and assess the immune status of calves for predicting the yield of cow milk. The results obtained by us require further confirmation in a more significant number of animals. Встановлено позитивний взаємозв’язок між довічним виходом молока та імунобіологічними показниками крові телят. Найбільша кореляція була між показниками молочної продуктивності та бактерицидної активності сироватки крові (r = 0,63-0,69, P <0,05). Зв'язок між клітинними факторами захисту організму (фагоцитарною активністю нейтрофілів) і вмістом імуноглобулінів класів G і M з ознаками молочної продуктивності був відповідно r = 0.31-0.41 і r = 0.58-0.63 (P <0.05). Дослідження імунного статусу телят з метою прогнозу молочної продуктивності корів є перспективними, однак вимагають підтвердження на більш значній кількості тварин.
Вихід молока в українських голштинів пов’язаний з імунобіологічними показниками крові телят
Милостивий Роман Васильович https://orcid.org/0000-0002-4450-8813 Антоненко Петро Павлович https://orcid.org/0000-0003-1469-0121 Василенко Тетяна Олександрівна https://orcid.org/0000-0002-2004-193X
Keywords: correlation; кореляція; calves; телята; cows; корови; blood; кров; milk yield; вихід молока